-2(-9n-8)=-(-10n-8)

Simple and best practice solution for -2(-9n-8)=-(-10n-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-9n-8)=-(-10n-8) equation:



-2(-9n-8)=-(-10n-8)
We move all terms to the left:
-2(-9n-8)-(-(-10n-8))=0
We multiply parentheses
18n-(-(-10n-8))+16=0
We calculate terms in parentheses: -(-(-10n-8)), so:
-(-10n-8)
We get rid of parentheses
10n+8
Back to the equation:
-(10n+8)
We get rid of parentheses
18n-10n-8+16=0
We add all the numbers together, and all the variables
8n+8=0
We move all terms containing n to the left, all other terms to the right
8n=-8
n=-8/8
n=-1

See similar equations:

| -(p+4)=-2(2p+8) | | 0.25(4x-3)=0.05(20x-9) | | 3^1/4×2^3/4=x | | 4(m+6)=8(m+1) | | 12x-2(12x-2)=-10(7x-12) | | (5u-30)(u^2+10u+24)=0 | | x/5=13/10 | | x^2=10√6 | | -3r+8r=6(1+r)-6(1+4r) | | 4^x-6.2^x=16 | | -11-2(1+9v)=-3(9v+10)+8v | | 6(a-9)=9(a-4) | | 8÷10=x÷100 | | -2(1+3m)-3(m+11)=2-11m-7 | | x^2-5x-1000=0 | | -(x-3)=-x-3 | | -12(9+2p)=-4(8p+9) | | 7t^2+28t+56=140 | | X^2+3x-4=2x+4 | | 7k-40=7(k-7) | | -6p+2p=6(2p-12)-4(p-9) | | 6=1/8=a | | 25w=50 | | x(x+2)/2=84 | | F(x)=3x2+6x+6 | | 19=9-y | | 2/3+4y=0.6 | | 2x^2+3x-9=204 | | F(0)=5n^2+2n | | 0.2(t+7.8)=16.5 | | F(n)=5n^2+2n | | 2/9x+1/3=-1/3x+1/3 |

Equations solver categories